Praktika ng Pagtulong sa Pamahalaang Lokal: Kasong Pag-aaral sa Bulacan - Veneracion, Ma. Corazon J. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 1 No 2 (2000), 2007)
This paper aims to construct new concepts for the practice of social work profession in local government settings based on the theory of social construction through the process of indigenization. Social construction theorizes that knowledge is shaped, defined, argued, and negotiated in and through interaction of human beings as members of a collective (Berger & Luckmann, 1967; Sarbin & Kitsuse, 1995). Indigenization refers to knowledge production by native encounter with foreign ideas, either by adaptation or adoption (Enriquez, 1992; Fernandez & Alegre, 1988). Methodologically, indigenization is grounded on a triangulation of field research techniques, namely, dialogue-interviews for life stories, journal accounts of non-participant observations, and focus group discussions. Twenty out of 24 municipal social welfare officers (all women), four selected mayors (all men) and 20 clients (mostly women) participated in the investigation, together with the research team and a panel of discussants from the academe and the DSWD Public Information Office. The study seeks to (1) find out the social worker's responses to the problems that clients present to the office, not necessarily those of her own discovery; (2) describe the helping consciousness of social workers, mayors, and clients included; and (3) reconceptualize social work practice in local governance as a collective effort among social workers themselves. In normal times and community life, villagers generally rely on their own kins and kindred spirit for support, not on bureaucracy. In critical times, villagers look for help from the municipal officials elected every three years. The social welfare officer is useful to the political leadership that banners the vision of social transformation in behalf of the electorate. The findings depict the social world of the munisipyo. The social worker that the civil service commission refers to as "social welfare officer" delivers services and practices her profession in a socio-political milieu. Her office serves as an extension of the mayor's. Shee keeps a balancing act between the mayor and staff, the sanggunian or municipal council, and the clients as individuals, groups, or communities. The findings also show the need to forge partnerships with NGOs, and to sustain network support systems within and outside the munisipyo. To affirm local empowerment, as in shared decision-making, vague images of an enabler or a service dispenser may yet shift and refocus to capability-builder, social advocate, resource-mobilizer, mediator-negotiator, or data-based program manager for a competitive edge. By locating citizen participation in municipal flagship policies and programs, the practitioner opens doors for constituents and civil society. All these efforts pave the road towards integrative and development visions that hold the well-being of the common tao fundamental. The study recommends a transformative journey for the social worker in search of the social psychology of pagtulong, i.e., an indigenized concept appropriate for the reinforcement of the Filipino social self.